2016
DOI: 10.1037/apl0000145
|View full text |Cite
|
Sign up to set email alerts
|

Individual deals within teams: Investigating the role of relative i-deals for employee performance.

Abstract: The authors extend i-deals theory to an individual-within-a-team context. Drawing upon social comparison theory, they contend that individuals will react to their own i-deals within the context of group members' i-deals. Therefore, they examine the role of relative i-deals (an individual's i-deals relative to the team's average) in relation to employee performance. Furthermore, integrating social comparison theory with social identity theory the authors assert that the behavioral outcomes of relative i-deals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 99 publications
0
80
1
Order By: Relevance
“…These findings provide several contributions to both the LMX and workplace entitlement literatures. First, while previous research has found a direct relationship between LMXSC and follower outcomes (Vidyarthi et al ., , ), to our knowledge, ours are the first studies to test a mediator of LMXSC. Across both studies, we found that LMXSC appears to drive followers’ feelings of obligation towards their leader, rather than LMX quality.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These findings provide several contributions to both the LMX and workplace entitlement literatures. First, while previous research has found a direct relationship between LMXSC and follower outcomes (Vidyarthi et al ., , ), to our knowledge, ours are the first studies to test a mediator of LMXSC. Across both studies, we found that LMXSC appears to drive followers’ feelings of obligation towards their leader, rather than LMX quality.…”
Section: Discussionmentioning
confidence: 80%
“…While LMXSC appears to offer important explanatory power to LMX theory, to date, empirical research investigating its effects has been scarce. The few empirical studies exploring LMXSC have focused on its main effect on followers’ behavioural outcomes (Vidyarthi et al ., , ). As such, we have limited knowledge about the nomological network of variables to which LMXSC is related and the underlying psychological mechanisms that explain the process by which LMXSC influences follower work outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the type of i-deals, the level of the i-deals may also cause some negative effects. Generally, receiving a greater level of task i-deals than coworkers can signal employees' value to, and relative social standing in, the organization (Ng & Lucianetti, 2016;Vidyarthi et al, 2016), however receiving a lower of task i-deals than others can have the opposite effect, such that employees feel less valued and suffer a decline in perceived status and self-worth. That is to say, employees' upward comparison of task i-deals (with their coworker) is positively related to their emotional exhaustion (Kong et al, 2018).…”
Section: Negative Effectsmentioning
confidence: 99%
“…In contrast, a collective-focused leadership climate promotes a group identity, collaboration and reciprocal exchange relationship between coworkers (e.g., Chun, Cho & Sosik, 2016). Research shows that the salience of the group identity decreases effects of i-deals (Vidyarthi et al, 2016). Thus, in organizations with a low collective-focused leadership climate, i-deals should influence collective OCBI, causing the inverted U-shaped relationship.…”
Section: The Role Of Leadership Behaviormentioning
confidence: 99%
“…I-deals are defined as individually negotiated employment arrangements that benefit both the employee and the employer (Rousseau, 2005). Previous research has mainly focused on positive effects of i-deals on individual employees who receive i-deals and only initial studies have applied multi-level methods to examine i-deals in a team or unit context (Bal & Boehm, 2017;Liao, Wayne, Liden, & Meuser, 2017;Vidyarthi et al, 2016). Thus, a huge gap in research remains because scholars have not yet studied i-deals from an organizational perspective and examined potential positive or negative effects of i-deals on organizations (Bal & Boehm, 2017).…”
Section: Introductionmentioning
confidence: 99%